THE IMPORTANCE OF PRACTICAL ORIENTATION IN INCREASING MOTIVATION AND IMPROVING LEARNING OF EDUCATIONAL CONTENT AMONG MEDICAL STUDENTS - Kholbekov Bakhodir Kuchkorovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
One of the unique features of teaching in medical universities is the absence of the method of “Learning from mistakes”. Based on the psychological characteristics of students of higher medical schools in the study of basic and clinical sciences, taking into account the experience of leading foreign medical schools in the field of student training, as well as the modern practice of teacher training institutions in the Republic of Uzbekistan and the trend to reform medical education, the introduction of medical sciences, the goal can be achieved through various games. One of the methods of formation of motivation for learning are business and role-playing games, modeling reality and representing a sequence of actions to be performed to achieve a certain result.